Perancangan Sistem Informasi Manajemen Barang Bekas Daur Ulang Berbasis Web Menggunakan Framework Laravel - Aznur, Mahzura; Putri, Raissa Ramanda; Sinaga, Imam Adlin (Teknik Informatika Fakultas Ilmu Komputer, 2025)
The rapid advancement of technology has driven the use of management information systems in all sectors, particularly in business, to facilitate the recording, storage, management, and provision of reports. This includes in the field of recycled goods collection. UD. Melati is one of the trading businesses that focuses on the collection and processing of data on used goods. However, in its activities, UD. Melati has not yet adopted a computerized system. As the volume of goods increases, the reliance on notebooks has become less practical and introduces risks, such as loss and damage. A web-based recycled goods management information system can help control operations and simplify data management. This web-based application is built using the Laravel Framework to enhance web development, making it more attractive and user-friendly. Laravel also offers various advantages, particularly in terms of security, making it an ideal choice for implementing a recycled goods management information system.